Grain quality evaluation of japonica rice effected by cultivars, environment, and their interactions based on appearance and processing characteristics. Issue 4 (24th February 2021) - Xia, Yujie; Sun, Yuying; Yuan, Jian; Xing, Changrui
Abstract: Appearance and processing characteristics of 45 japonica rice samples, collected from different regions in Jiangsu province, were investigated and evaluated in this study. Specifically, the chalkiness degree had been presented significant differences among different cultivars and regions. The average chalkiness degree varied from 6.81% to 15.34% for different regions and from 1.93% to 28.31% for different cultivars. The minimum head rice rate of cultivars from four regions, NJ9108 (HA), was 80.5%. The AC of CNG10, HD5, and PJ surpassed 13.68% and lower than 11.33% for the others. The protein content ranged from 6.1% to 11%, and the taste value was significantly different among cultivars. In addition, the RVA curves of the samples were similar, but the peak viscosities of NG8 and NJ5055 were higher than others, and there were significant differences in RVA traits among regions. Cultivars were the main reasons for the difference in appearance and processing quality of japonica rice, while environmental factors had leaded to the change of rice composition, texture, and gelatinization. Abstract : We collected 45 high‐quality japonica rice samples for quality analysis. Cultivars were the main reasons for the difference in appearance and processing quality of japonica rice, and environmental factors had leaded to the change of rice AC content, texture, and gelatinization.